The Influence of Independence, Integrity, and Professionalism on Audit Quality With Auditor Ethics as A Moderating Variable at BPK RI West Sumatra - Murdiawati Murdiawati; Hamdani Hamdani (Publikasi Indonesia, 2025)
This study aims to examine the influence of independence, integrity, and professionalism on audit quality, with auditor ethics as a moderating variable. The study adopts a quantitative research design with survey methods. Data were collected through a validated and reliable questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The population consists of 128 auditors at BPK RI, West Sumatra Regional Office, with a final sample of 122 respondents after data filtering. The results indicate that independence, integrity, and professionalism significantly influence audit quality. Furthermore, auditor ethics strengthens the relationship between integrity and audit quality, highlighting the critical role of ethics in enhancing audit outcomes. This study contributes to audit theory development by emphasizing the moderating role of auditor ethics in the relationship between integrity and audit quality. The findings also provide practical insights for BPK RI to improve financial audit quality by reinforcing ethical standards, integrity, and professionalism among auditors.